Child and adolescent psychiatry staff's knowledge on pain management. (July 2023) - Geremek, Adam; Ruby, Lisa; Lindner, Clemens; Niederberger, Uwe; Schild, Ursula; Jung, Martin; Soyka, Oliver; Siniatchkin, Michael
Objective: To assess the level of child and adolescent psychiatric staff's knowledge regarding pain management, to determine group differences between the medically more educated (physicians, nurses) and the less educated (psychologists, educators, special therapists) and to investigate the influence of gender, age, or professional experience as well as staff's own pain experiences. Methods: A total of 193 staff members from different professional backgrounds from three independent child and adolescent psychiatry clinics in Northern Germany were tested using the German version of the Pediatric Nurses' Knowledge and Attitudes Survey Regarding Pain Shriner's revision (PNKAS-Sr). Results: In total, the staff scored correctly 66% of the inventory questions. There was no difference between medically more educated and less educated staff members regarding the knowledge of pain management. The main factors influencing PNKAS score were age, profession, and pain education training. Conclusions: Although chronic pain is not one of the main aspects of continuing education in child and adolescent psychiatry, the resulting level of knowledge was comparable to results of similar surveys with paediatric staffs. Nevertheless, further education is needed to enhance knowledge and understanding of children's pain in child psychiatry staff in order to professionally treat patients with chronic somatic and mental illnesses.